Assessment of high performance SAPO‐34/S‐PEEK composite coatings for adsorption heat pumps. Issue 12 (15th October 2020) - Calabrese, Luigi; Palamara, Davide; Bruzzaniti, Paolo; Proverbio, Edoardo
Abstract: In this work, a new composite adsorbent coating on aluminum support, based on SAPO34 zeolite filler embedded into sulfonate polyether ether ketone matrix is investigated for adsorption heat pumps (AHP) applications. Composite zeolite/polymer mixtures, with 80–95 wt% content of SAPO‐34 zeolite filler have been prepared and coated on aluminum substrates. The as prepared coatings showed a pull‐off adhesion strength up to 2.0 MPa, significantly higher than conventional values of composite zeolite coatings reported in the literature. Scanning electron microscopy analysis demonstrated that the coating has a homogeneous morphology with zeolite filler well interconnected in the composite coating structure. Water adsorption isobars were carried out at equilibrium in the temperature range 30–120°C. The best adsorption performances for AHPs applications were observed for the PZ‐95 batch, where a maximum water uptake of ∼29.0 wt% was reached, highlighting that the polymer matrix presence does not alter the zeolite adsorption capability (31.3 wt%). Abstract : In Adosrption Heat Pumps (AHP) coated adsorber is an eligible choice in order to exalt system efficiency. In this paper a zeolite‐S‐PEEK composite coating was investigated on this concern. The material exhibited good mechanical performances and suitable adsorption performances for AHP applications.